Diffusion Tensor Imaging Shows Different Topographic Involvement of the Thalamus in Progressive Supranuclear Palsy and Corticobasal Degeneration - Erbetta, A. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: In progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD), postmortem studies show different topographic involvement of the thalamus, basal ganglia, and their cortical connections. Diffusion tensor imaging (DTI) is an MR imaging technique sensitive to gray and white matter microstructure integrity. This study was performed to determine whether DTI may demonstrate microstructural differences between PSP and CBD, particularly within the thalamus and its cortical connections. MATERIALS AND METHODS: Nine patients with probable PSP, 11 with probable CBD, and 7 controls formed the study group. Apparent diffusion coefficient average (ADC(ave)) and fractional anisotropy (FA) values were measured in regions of interest positioned in the ventrolateral (motor), medial, anterior, and posterior regions of the thalami, basal ganglia, fronto-orbital white matter, cingulum, supplementary motor area (SMA), and precentral and postcentral gyri in patients and controls. RESULTS: In PSP, ADC(ave) values were increased in several areas: the thalamus, particularly in its anterior and medial nuclei; cingulum; motor area; and SMA. FA values were particularly decreased in the fronto-orbital white matter, anterior cingulum, and motor area. In CBD, ADC(ave) was increased in the motor thalamus, in the precentral and postcentral gyri, ipsilateral to the affected frontoparietal cortex, and in the bilateral SMA. FA was mainly decreased in the precentral gyrus and SMA, followed by the postcentral gyrus and cingulum. CONCLUSIONS: In patients with PSP, thalamic involvement was diffuse and prevalent in its anterior part, whereas in CBD involvement was asymmetric and confined to the motor thalamus. DTI may be useful in the differential diagnosis of these 2 parkinsonian disorders.